The microtubule-associated protein She1 regulates dynein-mediated spindle positioning in budding yeast - Ecklund, Kari, author; Markus, Steven, advisor; DeLuca, Jennifer, committee member; Peersen, Olve, committee member; Krapf, Diego, committee member (Colorado State University. Libraries, 2020)
Microtubules are polar filamentous proteins part of a complex cytoskeletal network within cells that provides an organized interface with which motors use to transport vesicular cargoes and organelles, and mediate positioning of the mitotic spindle during cell division. There are two groups of molecular motor proteins that use microtubules as a track: (1) kinesins, the predominant anterograde motors and which are represented by six distinct different motors in budding yeast and (2) dynein, the predominant retrograde motor to which there is only one, cytoplasmic dynein, in budding yeast. Regulation of motor proteins is paramount to ensure that these various functions are achieved efficiently in a time and space-sensitive manner. There are many ways microtubules regulate their track, including through a class of highly diverse proteins called microtubule-associated proteins (MAPs), one of which in budding yeast is She1. In budding yeast, the only currently known role of cytoplasmic dynein is positioning the mitotic spindle during cell division. To direct the polarized movement of the spindle towards the daughter-cell, dynein relies on the MAP She1. To understand the mechanism by which She1 may regulate dynein-mediated spindle positioning, we first characterized the effects of She1 on dynein motility using recombinant protein. Our results demonstrated that She1 affects dynein motility by enhancing dynein-microtubule binding through simultaneous interactions with the dynein microtubule binding domain (MTBD) and the microtubule. From our in vitro data, we suggested a model where She1 assists dynein force generation to pull the large nucleus into the narrower bud neck connecting mother and daughter cells. However, we tested this model in vivo and found no such effects on nuclear translocation success, leaving us to investigate an alternative model where She1 polarizes spindle movements towards the daughter cell through inhibiting dynein activity in the mother cell. We explored this model in vivo using a comprehensive analysis of dynein-mediated spindle movements which revealed She1 ensures dynein in the daughter cell maintains bud neck proximity by inhibiting dynein activity and the initiation of dynein-mediated spindle movements in the mother cell. Moreover, we find that this process depends on She1 binding to aMTs in the mother cell and not spindle microtubules where She1 also localizes. Finally, we provide evidence that She1 requires the MTBD of dynein for some aspects of this inhibition, reconciling, in part, our in vitro and in vivo data. Our data provides a fascinating new mechanism of regulation by a MAP and suggests a new angle to approach future exploration of MAP-mediated regulation in higher eukaryotes.
Keywords: dynein; microtubule; She1; MAP; budding yeast; microtubule-associated protein